Serum carbohydrate antigen 125 levels and incident risk of type 2 diabetes mellitus in middle-aged and elderly Chinese population: The Dongfeng–Tongji cohort study. (September 2019) - Yu, Caizheng; Lei, Qing; Wang, Jing; Han, Xu; Wang, Fei; Yuan, Jing; Yao, Ping; Wei, Sheng; Wang, Youjie; Liang, Yuan; Zhang, Xiaomin; Guo, Huan; et al.
Objectives: The aim of this study was to investigate the association between serum carbohydrate antigen 125 concentrations and incident type 2 diabetes mellitus risk in a prospective cohort. Methods: We included 18, 983 eligible participants aged 63.1 years derived from the Dongfeng–Tongji cohort at baseline from September 2008 to June 2010, and they were followed until October 2013. Cox proportional-hazards models were used to estimate the hazard ratios and 95% confidence interval of type 2 diabetes mellitus incidence in relation to carbohydrate antigen 125 concentrations. Results: In all, 1594 incident cases of type 2 diabetes mellitus were observed after a median follow-up of 4.6 years. Carbohydrate antigen 125 concentrations were categorized into four groups according to the quartiles of distribution: <1.1, 1.1–5.6, 5.6–10.0 and ⩾10 U/mL. Compared with participants in the lowest quartile, the hazard ratio (95% confidence interval) of type 2 diabetes mellitus was 0.97 (0.81–1.15), 1.23 (1.05–1.45) and 1.48 (1.27–1.74) for quartile 2–quartile 4 of carbohydrate antigen 125 concentrations after adjustment for potential confounders ( p for trend < 0.001). With per–standard deviation increase in carbohydrate antigen 125 levels, the hazard ratio of type 2 diabetes mellitus increased 12% (95% confidence interval, 8–16). Conclusion: Findings from this study indicated that serum carbohydrate antigen 125 concentrations were positively correlated with incident type 2 diabetes mellitus risk among a middle-aged and elderly Chinese population.